An Information System for Law Integrating Ontological Bases with a Legal Reasoner Chatbot - Monteiro, Lucas Henrique de Assis; Rodrigues, Cleyton Mário de Oliveira; Sousa, Aêda Monalliza Cunha de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: The Semantic Web aims to assign meanings to resources available on the internet so that humans and computers can understand them. It can be used in the most diverse contexts, facilitating the development of systems where expert knowledge is formalized through logical-mathematical resources, mitigating potential inconsistencies, and promoting more human-friendly interaction services. Problem: The existence of semantic anomalies (use of rhetorical language, polysemy and inaccuracies) in the Brazilian Legal Domain enables the use of Semantic Web standards and technologies to mitigate these problems. Solution: This work deals with the development of an Information System that uses resources from the Semantic Web for the formal representation and the realization of legal inferences about Crimes Against Property. SI Theory: The Behavioral Decision Theory was approached, mainly in the incorporation of real patterns of decision making. Method: Bibliographic and documentary research methods were used to list the main concepts related to the Criminal Types investigated. The research is prescriptive and has a quali-quantitative approach. Summary of Results: A prototype system is presented, integrating ontologies of Brazilian Law with a chatbot that enables interaction with users in natural language, as well as performing reasoning tasks based on the knowledge formalized in these ontologies. Contributions and Impact in the IS area: The research will contribute to the automation of decision-making processes involving crimes against property, serving as an aid for professionals or law students and for legal simulations by ordinary people. Furthermore, it will serve as a reference for the development of other information systems with similar objectives in other contexts.